Perancangan dan Evaluasi Aplikasi MAVA Menggunakan Metode User-Centered Design di Kota Malang - Budijono, Hana Angelyn; Ilmananda, Asri Samsiar (CV. Information Technology Training Center - Indonesia (ITTC), 2026)
This study aims to design and evaluate the MAVA (Malang Vacation App) prototype using User-Centered Design (UCD). MAVA is an integrated digital tourism platform providing information on destinations, culinary, and events in Malang City. The research includes five stages: plan, analysis, design, prototype, and evaluation. Data were collected through interviews and questionnaires involving tourists, business owners, and Malang Tourism Office representatives. The prototype was created using Figma and evaluated using System Usability Scale (SUS) with 20 respondents. Results showed MAVA obtained an average SUS score of 79, categorized as